Mass angular scattering power method applied to the therapeutical electron beams - İşbakan, Fatih. (Thesis (M.S.) - Bogazici University. Institute of Biomedical Engineering, 1997., 1997)
A method for determining the kinetic energies of therapeutical electron beams is described. The theoretical basis of the mass angular scattering power method is analyzed. The kinetic energy of therapeutical electron beams is determined from the Gaussian spread of a pencil beam. The pencil beam is obtained from a broad electron beam by using a simple technique. The data taken with a "closed collimator" are subtracted from those measured with the "open collimator" in order to isolate the pencil beam dose distribution.The spatial spread of a pencil electron beam in air is ,as predicted by the Fermi-Eyges Theory,is Gaussian whose variance is a function of the mass angular scattering power ,which in turn is related to the kinetic energy . The dose distribution is measured by an ion chamber which is moved by an "empty" water phantom system.The energies obtained by the mass scattering power method in air are significantly close to measured values obtained with the range method in water.The mass angular scattering power method is driven from the inelastic collisions in air and uses a probabilistic approach while the range method uses empirical formulas.
Keywords: Radiotherapy.; Electron beams -- Therapeutic use.